(untitled) (SAARC Journal of Agriculture, 2017)
The proximate composition, fatty acid, amino acid and fat soluble vitamins of Indian climbing perch, Anabas testudineus, locally called Koi were assayed in relation to its body weight. The fish samples were collected from different geographical locations and were grouped as small (10-50g) and big (52-150g) sizes. The proximate composition, essential amino acid (EAA) and non-essential amino acid (NEAA) contents in Koi did not differ significantly between the groups. The monounsaturated fatty acid (MUFA) content was significantly (P<0.05) higher in bigger sized Koi. The polyunsaturated fatty acid (PUFA) content was 23.67±0.85 and 13.62±1.02 (%) respectively in the small and big sizes of Koi, while the docosahexaenoic acid (DHA) was significantly higher in small Koi. The vitamin A content was 85.77±0.35 and 93.90 ±1.34 (I.U./100g) respectively in small and big Koi. Vitamin D content was significantly higher in small Koi compared to big one. Vitamin E and K were significantly (P<0.05) higher in big Koi. The results indicated that Anabas testudineus is a good source of protein, fat, vitamins, amino acids and fatty acids. SAARC J. Agri., 15(1): 99-109 (2017)